Serum anti-Müllerian hormone levels are associated with perinatal outcomes in women undergoing IVF/ICSI: A multicenter retrospective cohort study - He, Yi-Chen; Su, Kai-Zhen; Cai, Jie; Meng, Qing-Xia; Wu, Yan-Ting; Huang, He-Feng (Frontiers in Endocrinology, 2023)
Introduction: Anti-Müllerian hormone (AMH) level has long been considered as a serum biomarker of ovarian reserve clinically, while emerging data suggest that serum AMH level may also predict pregnancy outcomes. However, whether pregestational serum AMH levels are related to perinatal outcomes among women undergoing in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI) cycles is unknown. Objective: To explore the association between different AMH levels and perinatal outcomes in women with live births in IVF/ICSI. Methods: This multicenter retrospective cohort study was conducted among three different provinces in China, from January 2014 to October 2019. A total of 13,763 IVF/ICSI cycles with 5657 live-delivery pregnant women and 6797 newborns were recruited. Participants were categorized into three groups according to the <25th (low), 25 to 75th (average), and >75th (high) percentile of serum AMH concentration. Perinatal outcomes were compared among groups. Subgroup analyses were conducted based on the number of live births. Results: Among women with singleton deliveries, low and high AMH levels increased the risk of intrahepatic cholestasis of pregnancy (ICP) (aOR1=6.02, 95%CI: 2.10-17.22; aOR2=3.65, 95%CI:1.32-10.08) and decreased the risk of macrosomia (aOR1=0.65, 95%CI:0.48-0.89; aOR2=0.72, 95%CI:0.57-0.96), while low AMH reduced the risk of large for gestational age (LGA, aOR=0.74, 95%CI:0.59-0.93) and premature rupture of membrane (PROM, aOR=0.50, 95%CI:0.31-0.79)compared with the average AMH group. In women with multiple deliveries, high AMH levels increased the risks of gestational diabetes mellitus (GDM, aOR=2.40, 95%CI:1.48-3.91) and pregnancy-induced hypertension (PIH, aOR=2.26, 95%CI:1.20-4.22) compared with the average AMH group, while low AMH levels increased the risk of ICP (aOR=14.83, 95%CI:1.92-54.30). However, there was no evidence of differences in preterm birth, congenital anomaly, and other perinatal outcomes among the three groups in both singleton and multiple deliveries. Conclusions: Abnormal AMH levels increased the risk of ICP regardless of the number of live births for women undergoing IVF/ICSI, while high AMH levels increased the risks of GDM and PIH in multiple deliveries. However, serum AMH levels were not associated with adverse neonatal outcomes in IVF/ICSI. The underlying mechanism warrants further investigation.